Engineering education in OIC countries: direction to move - Kabbashi, Nassereldeen Ahmed (2015)
Engineering has always played a key role in wealth design. Engineering education in the Organization of Islamic Cooperation (OIC) member countries is not new in its starting as it almost as same as most other parts of the world when starting with conventional engineering programme as civil, chemical electrical and mechanical engineering programmes, which focused mainly at that time on engineering design, manufacturing, testing and production. But with the development of human and market need, new directions of engineering courses has been setup, today fields of engineering has extended to cover different engineering skill, with more than 40 engineering categories from mechanical to aerospace, material to safety, electrical to telecommunications, civil to environmental, and more, engineering fields have constricted and advanced to key areas of engineering areas’. As a result many issues and challenges facing the engineering education development in OIC countries need way forward. This paper will focus on this development together with issues and challenges for way forward.